PENGARUH PARTISIPASI ANGGARAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI - Ramadan, Mochammad Tanzyar Praja; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis researchis meant to examine the influence of participatory budgeting preparation and organizational culture to theemployee performanceof the Revenue,Financial and Assets Management OfficesSidoarjo district. The method uses quantitative method. The sample collection technique has been done by using purposive sampling. The dataisoriginated from 45 questionnaires which have beenissued to the head of the subsection, head of division, head of section, and employees who are involved in budget preparation participation. Thecollected data has been processed by using multiple linear regression analysis and the SPSS program. The result of the research indicates that participatory budgeting preparationgive positive influence to the employee performance. It describes that the high level of participatory budgeting preparation, the employees will be more responsible and motivated in theirtasksin whichit will improve the employee performance. Organization culture gives positive influence to the employee performance. It shows that good organization culture and the availability of information which relevant to the task enables subordinates to exchange information with superiors, so it can create good decision in the participatory budgeting preparation, and finallyit supports the employee performance.Keywords: Participatory budgeting preparation, organizational culture, employee performance